The long-term in vivo behavior of polymethyl methacrylate bone cement in total hip arthroplasty. - Hiroyuki Oonishi; Haruhiko Akiyama; Mitsuru Takemoto; Toshiyuki Kawai; Koji Yamamoto; Takao Yamamuro; Hironobu Oonishi; Takashi Nakamura (Acta Orthopaedica, 2011)
Background and purpose The long-term success of cemented total hip arthroplasty (THA) has been well established. Improved outcomes, both radiographically and clinically, have resulted mainly from advances in stem design and improvements in operating techniques. However, there is concern about the durability of bone cement in vivo. We evaluated the physical and chemical properties of CMW1 bone cements retrieved from patients undergoing revision THA. Methods CMW1 cements were retrieved from 14 patients who underwent acetabular revision because of aseptic loosening. The time in vivo before revision was 7–30 years. The bending properties of the retrieved bone cement were assessed using the three-point bending method. The molecular weight and chemical structure were analyzed by gel permeation chromatography and Fourier-transform infrared spectroscopy. The porosity of the bone cements was evaluated by 3-D microcomputer tomography. Results The bending strength decreased with increasing time in vivo and depended on the density of the bone cement, which we assume to be determined by the porosity. There was no correlation between molecular weight and time in vivo. The infrared spectra were similar in the retrieved cements and in the control CMW1 cements. Interpretation Our results indicate that polymer chain scission and significant hydrolysis do not occur in CMW1 cement after implantation in vivo, even in the long term. CMW1 cement was stable through long-term implantation and functional loading.